Implementing Best Practice in Training Problem-Based Learning Tutors - Jill Rose Johnson (Halla Newcastle Education and Research Center, 2021)
Purpose In order to implement problem-based learning (PBL), extensive staff training is required. The purpose of this study was to qualitatively evaluate the efficacy of a training programme for inexperienced PBL tutors. Methods Data included anonymous feedback from programme participants, semi-structured interviews with programme participants, and feedback from students. Results Data from these independent sources were analysed, resulting in three main themes that painted a comprehensive picture of the success and limitations of the PBL tutor training programme: I) pedagogical knowledge of PBL was obtained but needs to be reinforced by practice; II) the mock tutorial was a relevant experience; III) a written PBL tutor guide supports training efforts. Conclusions Using diverse sets of data, this study demonstrated that the acquisition of pedagogical knowledge is contextual and partial, and multiple sources of knowledge are required to achieve a complete and interpretable picture of the subject.